Current and Future Global Research Trends in Osteosarcoma: A Bibliometric Analysis of Surgical Strategies and Recurrence - Ridha Aswina Dalimunthe; Rhyan Darma Saputra; Rieva Ermawan ((JOINTS) Journal Orthopaedi and Traumatology Surabaya, 2026)
Background: Osteosarcoma is the most common primary malignant bone tumor, yet comprehensive mapping of its evolving research landscape remains limited. This bibliometric analysis aims to characterize global research trends, identify thematic hotspots, and delineate emerging directions in osteosarcoma research, with a particular focus on publications related to local control, recurrence, and wide surgical margins.Methods: Publications from January 2021 to April 2025 were retrieved from the Dimensions database using the terms “osteosarcoma,” “local control,” “recurrence,” and "wide margins." After screening, 498 eligible records were analyzed using Bibliometrix/Biblioshiny in RStudio and Microsoft Excel.Results: Publication output increased from 2021 to 2023, with China, the United States, and Japan as the leading contributors. Chinese institutions represented 23% of the top 50 productive organizations, whereas Canada, Austria, and Greece showed the highest international collaboration rates. Thematic mapping identified motor themes related to tumor classification, treatment, prognosis, and local recurrence; niche themes such as en bloc sacrectomy and 3D-printed reconstruction; and emerging themes including artificial intelligence-based risk prediction and early metastasis detection.Conclusions: This bibliometric analysis identifies a trend in osteosarcoma research toward technology -driven and precision-oriented surgical strategies, including AI-assisted risk stratification, 3D-printed reconstruction, and immunomodulatory perioperative approaches. These bibliometric trends suggest growing research interest in optimizing local control and minimizing recurrence, although their clinical impact remains to be validated through prospective studies. The findings provide a descriptive overview of current research directions and may inform future research prioritization.